2009
DOI: 10.1172/jci37405
|View full text |Cite
|
Sign up to set email alerts
|

Deficiencies in Chfr and Mlh1 synergistically enhance tumor susceptibility in mice

Abstract: Genetic instability, which leads to an accumulation of various genetic abnormalities, has been considered an essential component of the human neoplasic transformation process. However, the molecular basis of genomic instability during tumorigenesis remains incompletely understood. Growing evidence indicates that checkpoint with forkhead and ring finger domains (CHFR), a recently identified mitotic checkpoint protein, plays an important role in maintaining chromosome integrity and functions as a tumor suppresso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 80 publications
4
15
0
Order By: Relevance
“…The association between CHFR and Aurora A led to the ubiquitination of Aurora A and its destabilization in mouse embryo fibroblast cells in the presence of stress agents [26]. This is consistent with observations showing an inverse relationship between loss of CHFR function and Aurora A levels in CHFR -/-mouse embryonic fibroblasts (MEFs) [26], prostate [13] and breast [13,25] cancer cell lines as well as colorectal cancer samples [27].…”
Section: Possible Modes Of Action Of Chfr In Delaying Mitotic Entrysupporting
confidence: 87%
“…The association between CHFR and Aurora A led to the ubiquitination of Aurora A and its destabilization in mouse embryo fibroblast cells in the presence of stress agents [26]. This is consistent with observations showing an inverse relationship between loss of CHFR function and Aurora A levels in CHFR -/-mouse embryonic fibroblasts (MEFs) [26], prostate [13] and breast [13,25] cancer cell lines as well as colorectal cancer samples [27].…”
Section: Possible Modes Of Action Of Chfr In Delaying Mitotic Entrysupporting
confidence: 87%
“…37,38 As observed in our study, CHFR methylation is often associated with microsatelliteunstable gastric cancers 39 and genetic inactivation of both MLH1 and CHFR in mice resulted in much increased susceptibility to tumor development including gastrointestinal cancers. 40 In our study, among the novel genes identified to be hypermethylated in gastric cancer, BRINP1 and SGCE showed significant correlation of expression with survival in gastric cancer. BRINP1 (BMP/RA-induced neural specific protein-1) is induced during differentiation of peripheral neurons and overexpression of BRINPs was shown to suppress cell cycle progression in non-neural cells, suggesting a possible tumor suppressor role.…”
Section: Discussionsupporting
confidence: 48%
“…Although both CHFR and MLH1 contribute to genomic integrity, they function through different mechanisms. CHFR deficiency triggers mild CIN and MLH1 deficiency leading to MSI (56). Recent data from Oh and colleagues 2009 (57) indicate that, in vitro, CHFR binds and downregulates HDAC1 thereby downregulating cyclin-dependent kinase inhibitor 1 and the metastasis suppressors, KAI1 and Cadherin-1.…”
Section: Discussionmentioning
confidence: 99%